2001
DOI: 10.1073/pnas.98.3.1176
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of gene expression profiles in normal and neoplastic ovarian tissue samples identifies candidate molecular markers of epithelial ovarian cancer

Abstract: Epithelial ovarian cancer is the leading cause of death from gynecologic cancer, in part because of the lack of effective early detection methods. Although alterations of several genes, such as c-erb-B2, c-myc, and p53, have been identified in a significant fraction of ovarian cancers, none of these mutations are diagnostic of malignancy or predictive of tumor behavior over time. Here, we used oligonucleotide microarrays with probe sets complementary to >6,000 human genes to identify genes whose expression cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
345
2
8

Year Published

2001
2001
2006
2006

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 587 publications
(375 citation statements)
references
References 20 publications
20
345
2
8
Order By: Relevance
“…Such studies have identified the gene coding for HE4, a secreted extracellular protease inhibitor, as a promising diagnostic marker (Ono et al, 2000) and pinpointed other genes that correlate with serous and mucinous histology (Schummer et al, 1999). A recent report (Welsh et al, 2001) analysed the expression levels of more than 6000 human genes in 27 ovarian tumours and four normal ovarian tissue samples using this technique. This study identified genes whose expression pattern distinguished between ovarian cancer of low and high malignancy and ranked other genes in terms of the diagnostic potential of their expression.…”
Section: Discussionmentioning
confidence: 99%
“…Such studies have identified the gene coding for HE4, a secreted extracellular protease inhibitor, as a promising diagnostic marker (Ono et al, 2000) and pinpointed other genes that correlate with serous and mucinous histology (Schummer et al, 1999). A recent report (Welsh et al, 2001) analysed the expression levels of more than 6000 human genes in 27 ovarian tumours and four normal ovarian tissue samples using this technique. This study identified genes whose expression pattern distinguished between ovarian cancer of low and high malignancy and ranked other genes in terms of the diagnostic potential of their expression.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this classifier allowed a lower ratio of errors/correctly classified (r ¼ 0.05) than the set of 126 genes. To validate the classifier, an additional independent test set of 23 primary culture samples and 137 arrays of surgical specimens from publicly available data sets derived from Affymetrix HuFL GeneChip platform (Welsh et al, 2001;Schwartz et al, 2002;Ouellet et al, 2005) were tested. The set of 23 primary culture samples contained two LMP serous ascites.…”
Section: Selection Of Genes Distinguishing Subclasses Of Ovarian Tumoursmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11] Gene expression fingerprints representing large numbers of genes may allow precise and accurate grouping of human tumors and may identify patients who are unlikely to be cured by conventional therapy. Consistent with this view, evidence has been provided to support the notion that poor-prognosis B-cell lymphomas and biologically aggressive breast and ovarian carcinomas can be readily distinguished by gene expression profiles.…”
mentioning
confidence: 99%